Optimizing Social Media as a Global Marketing Tool: Qualitative Analysis of Different Approaches in Enhancing the Image and Sales of Exported Products - Nazarudin, Muchamad Ilham; Wiwik Handayani (CV. Lenggogeni Data Publishing, 2024)
Research Aims: This research aims to explore the role of social media in global marketing, particularly in shaping brand image and increasing sales of exported products. It seeks to analyze how social media platforms are utilized to capture global market shares, foster sustained relationships with consumers, and develop positive brand perceptions. Additionally, it aims to investigate the intrinsic relationship between brand image and sales volume, focusing on the impact of a positive image on consumer interest and exported product sales. Design/Methodology/Approach: Utilizing a descriptive qualitative approach, this study delves into consumers' preferences, behaviors, and perspectives regarding exported products while analyzing factors influencing brand image and sales through social media platforms. The methodology involves a thorough literature review, drawing insights from academic sources and scholarly works related to social media's role in global marketing, exporting products, and brand image enhancement. Research Findings: The research findings emphasize prevalent social media approaches in global marketing, including targeting specific markets, leveraging appropriate platforms, content-centric strategies, and engagement-oriented approaches. Despite notable benefits, around 30% of companies appeared to underutilize these strategies. Furthermore, a clear correlation between effective social media strategies and the positive image of exported products was identified. Successful social media applications, illustrated through case studies, highlighted the significance of internal understanding of target markets, crafting tailored content, and awareness of external factors like social media trends and cultural nuances. conclusion: This study underscores the pivotal role of social media in global marketing strategies, emphasizing the need for companies to adapt and align their approaches with internal and external market dynamics. The findings suggest that harnessing the potential of social media involves a comprehensive understanding of consumer behavior, market trends, and effective content strategies